Targeting of activated fibroblasts for imaging and therapy - Lindner, Thomas; Loktev, Anastasia; Giesel, Frederik L.; Kratochwil, Clemens; Altmann, Annette; Haberkorn, Uwe (EJNMMI radiopharmacy and chemistry, 2019)
Tumors form a complex environment consisting of a variety of non-malignant cells. Especially cancer-associated fibroblasts have been shown to have an important role for different aspects of malignant tumors such as migration, metastasis, resistance to chemotherapy and immunosuppression. Therefore, a targeting of these cells may be useful for both imaging and therapy. In this respect, an interesting target is the fibroblast activation protein (FAP) which is expressed in activated fibroblasts, but not in quiescent fibroblasts, giving the opportunity to use this membrane-anchored enzyme as a target for radionuclide-based approaches for diagnosis and treatment of tumors and for the diagnosis of non-malignant disease associated with a remodelling of the extracellular matrix.